(3JaSjQ ZQjH GdbQBf Ydi MQha GdeYLes - (3eMeO Hf YHO GdYRjR GdSLSJjf, CHh HcQs ((3WHjH GHf dDdD GdcMGNi s)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hUdi Gddg Ydi eMeO QShdg hYHOg gPG GdcJGH ZQjH GdbQBf Ydi MQha GdeYLe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs